Sustainability Balance Scorecard: Literature Review and Clustering of Performance Indicator - Trisyulianti, Erlin; Suryadi, Kadarsah; Prihantoro, Budi (IPB University, 2024)
Answering the challenges of sustainable development, companies require an integrated approach to performance management in economic, social, and environmental aspects. This approach is not only profit-oriented but also addresses the needs of human welfare, social, and environmental concern. The approach also includes the ability to link strategy with action. Therefore, it is important to apply the sustainability Balanced Scorecard (SBSC) in performance management. The research aims to study the development of SBSC studies for the last decade. A systematic literature review has been conducted to identify, evaluate, and interpret SBSC based on previous research. The results described publication map, the taxonomy of research, and meta-analysis of SBSC performance indicators.